Analysis of Inequality and Classification of Regency/City Economic Development in The Riau Archipelago Province, 2016-2021 (Journal of Economic Education, 2023)
The role of local government in the era of regional autonomy is to have the authority to develop the regional economy in accordance with the potential of the region. So that it is expected that the formation of a strategy or policy is more appropriate in overcoming regional economic problems, considering that each region has different economic growth and per capita income. This study aims to find out inequality in economic development and determine the classification of districts/cities in the Riau Archipelago Province for the period 2016 – 2021 using the Williamson Index approach and the Klassen Typology. Based on the results of the Williamson Index calculations in 2016 – 2021, it shows that the Riau Archipelago Province has experienced a decrease in the index number to 0.40. This condition indicates that there are government efforts to equalize economic development so that the disparity in economic development between districts/cities in the Riau Archipelago Province has decreased. Even so, inequality in economic development in this province still exists and needs to be corrected, one of which is through the concentration of economic activity in each region. Based on the results of the study using the Klassen Typology, it shows that most of the regencies/cities in the Riau Archipelago Province in the 2016 – 2021 period are included in relatively underdeveloped areas, namely; Karimun Regency, Lingga Regency, Bintan Regency and Tanjungpinang City. In addition, there are 2 districts that are included in the classification of developed but depressed areas, namely; Natuna and Anambas Regencies. Furthermore, the areas included in the classification of fast developing areas are; Batam city.